Development of Analytical Method for Cable-stayed Bridges Considering Local Damages Caused by Failure of Supporting Cables - Ahmed Ramadan Ahmed; Qais Abdulrahman Ali Qais; Nikolay A. Yermoshin (Structural Mechanics of Engineering Constructions and Buildings, 2024)
Bridge structures are often subjected to extreme conditions such as rough weather, earthquakes, impacts from traffic accidents, and even blasts. Such extreme loads can cause damage to the anchorage zones as a result of high stress concentration and can lead to cable loss. Such extreme loads can cause dam-age to the anchorage zones as a result of a highstress concentration and can lead to cable loss. One of the main targets of this study is to develop an analytical method that increases our understanding of the behavior of long-span cable-supported bridges in the case of the failure of one or several cables,through this method, a formula can be deduced to calculate dynamic amplification factor (DAF) more accurately, which could be useful for academic research. In this study, a parallel-load bearing system is considered as a conceptual model of long-span cable-supported bridges. The objective is to investigate the structural robustness of long-span cablesupported bridges in a cable-loss scenario. The conceptual model consists of a beam suspended from cables (tension elements). A simplified model is intentionally selected to make the analytical approach easier. If examining the simplified model shows a certain phenomenon, a similar phenomenon in more sophisticated models can also be expected. The study considers multiple cable failures and employs an analytical approach, developing an approximation function for stress magnification factor in cable break scenarios, using least squares method. The proposed approximation function is accurate and less than 5% error-free in all tested systems, except for minor β values, and increasing β reduces stress magnifica-tion factor. The parameter β influences the calculation of the cable load. For systems with high β values, smaller design loads are necessary, allowing long-span cable-stayed bridges to be segmented into zones with varying β values. This approach enables the determination of minimum design loads for each zone, ultimately reducing cable design costs in cases of cable loss.